(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Acute abdominal pain should always be evaluated quickly and accurately due to the possibility of urgent surgical intervention. We report a case of a woman with ovarian apoplexy while taking Clofit Citrate. The patient developed acute abdominal pain after coitus. The patient was diagnosed ovarian apoplexy with ovarian cyst using pelvic ultrasound. The main differential diagnosis of ovarian apoplexy in women of reproductive age is ectopic pregnancy and ovarian cyst torsion. In this article, we describe a rare case of ovarian apoplexy while taking the drug.